Psychology in Teaching of Psychology - Seguin, Carlos Alberto (1963)
When you start reading this work, I wish to clarify its scope and features. This is not a general consideration of the problem of the teaching of psychology, but a communication with precise and limited purpose: to account for an experiment in the teaching of medical psychology, its theoretical basis and its first results.